Hubungan Pengetahuan Wanita Usia Subur Tentang Kanker Serviks Dengan Keikutsertaan Dalam Melakukan IVA Test Di Puskesmas Tambusai Kabupaten Rokan Hulu Tahun 2018 - Wulandari, Sri (Jurnal Martenity and Neonatal, 2019)
Cervical cancer is a type of cancer occurring in areas, cervix and is the main cause of death among women. around the world 274.000 estimated deaths occur each year as a result of this disease, with an estimated around percent of new cases 89. in developing countries The main cause of cervical cancer is human papillomavirus ( ) hpv as the main cause of death among women worldwide in rescuing women that the victim, cervical cancer one of them is by effort to early detection methods visual inspection with acetic acid ( iva ), a method of iva is practical, screening method simple, and cheap. sensifitasnya high The purpose of this research to know the fertile woman knowledge of cervical cancer with participation in doing iva test center tambusai rokan upstream years 2018. The methodology quantitative research survey design analytic used the cross sectional time .Included in this study was a fertile totaling 81 the using tekhnik simple random sampling .Test chi square with standard significance (Î±=0,05 ) obtained value p value = 0,0001 (p<0,05) so ho turned down and ha accepted .The conclusion of this research is the relationship between knowledge of cervical cancer with participation in doing iva test at community tambusai district rokan the 2018.